A Monte Carlo model for predicting the erosion rate of EB PVD TBCs - Wellman, R. G.; Nicholls, John R. (Elsevier Science B.V., Amsterdam., 2004)
Since the introduction of electron beam (EB) physical vapour deposition (PVD) thermal barrier coatings (TBCs) and their application to moving components in the hot gas stream, erosion has become a prime concern. EB PVD TBCs, due to their unique columnar microstructure are far more strain tolerant than their plasma sprayed (PS) counter parts and can thus be used under more exacting operating conditions. It is under these operating conditions that erosion of the coated components is of primary importance. The main aim of this project was the development of a computer model capable of predicting the erosion rate of EB PVD TBCs under various different conditions relevant to engine operation. In order to do this it was first necessary to determine the erosion mechanisms of EB PVD TBCs as well as their mechanical properties. Steady-state erosion and single impact studies together with SEM were used to determine the erosion mechanisms. While nano-indentation techniques were used to obtain the hardness and the YoungÃ¢Â Â s modulus of the EB PVD TBC. All these findings were then used in the development of a Monte Carlo type computational erosion model capable of predicting the erosive wear rate of EB PVD TBCs under various conditions. The model which has been developed is capable of predicting the erosion rate of EB PVD TBC to within 30%, so long as the erosion falls within the defined mechanism. This can easily be checked against an erosion map which has been developed. This paper discusses the program and reports some results from running the program under various condition
Keywords: Erosion; Modelling; EB PVD TBC